Karakter Disiplin Siswa dalam Kegiatan Ekstrakurikuler Pendidikan Kepramukaan - Ratna Dila; Lukman Lukman; Dwi Anggraini (JURIDIKDAS, 2018)
Purpose of this study was to describe the character of the discipline of students in extracurricular activities Scouting Education in Elementary School 68 Bengkulu city, especially in the opening and closing ceremonies Penggalang Scouts practice. This study used a qualitative approach with descriptive methods. Subjects of research include coaches and assistant coaches Penggalang Scouts and Boy Scouts. Research instrument is observation and interview guides. Data collection techniques are observation, interviews, and documentation. Data were analyzed with the stages of data collection, data reduction, data display and conclusion. Test the validity of the data by triangulation of sources and techniques. The results showed that the activities of the opening and closing ceremony of the exercise, members have shown discipline in the activities of prayer and homage to the Red and White when hoisted or lowered. However, members of visible violation of the rules that is talking, do not wear the Scout Uniform Complete (SUC), delayed forming a line angkare, and less unprepared when members gather to hear the instructions given by the Primary. In the opening ceremony activities, readings Pancasila and Dasadarma performed in a loud voice, precise intonation and clear pronunciation. Based on the results of this study concluded that the discipline of members in the opening and closing ceremonies of exercise was seen although there are violations.